Personality and psychographics - Bhatnagar, Namita (Henry Stewart Talks, 2013)
Personality research, Freudian theory, Motivational research and consumption motives, Neo-Freudian theories, Trait theory, Brand personality, Animism and anthropomorphization, Lifestyles and consumption patterns, Lifestyle marketing perspective, Psychographic analysis, AIO dimensions, VALS framework, Geodemographic segmentation, Food cultures, Behavioral targeting